Carotid Endarterectomy in a Patient with Posterior Cerebral Artery Infarction: Influence of Fetal Type PCA on Atypical Clinical Course. (10th June 2015) - Kolukısa, Mehmet; Gürsoy, Azize Esra; Kocaman, Gülşen; Dürüyen, Hümeyra; Toprak, Hüseyin; Asil, Talip
Abstract : Fetal type PCA may positively affect clinical outcome in patients with ischemic stroke such as protection of a reserve blood flow capacity as well as negative effect on clinical outcome such as certain atypical pathological manifestations. We presented a patient with a posterior cerebral artery territory infarction due to an unexpected etiology as stenosis of internal carotid artery (ICA) with existence of fetal type PCA.